South-South Knowledge Exchange : A Natural Agenda for Latin America and the Caribbean - Quiñonez, Alfonso (2012)
South-South Cooperation (SSC) is a longstanding form of collaboration which has recently gained momentum, especially in the Americas. Two key elements explain the growing importance of SSC, its new modalities, and their contribution to triangular cooperation schemes.